Pay Attention to Biological Nanoparticles when Studying the Protein Corona on Nanomedicines. (8th June 2020) - Simonsen, Jens B.; Münter, Rasmus
Abstract: The protein corona of nanoparticles has in recent years received considerable attention, and even been postulated to be the missing link in the translation of nanomedicines from benchtop to bedside. We highlight the different types of biological nanoparticles present in blood that need to be considered in the protein corona research field. We map their size, density, and plasma concentrations, and use this information to stress potential challenges related to the isolation of nanomedicines—with a particular focus on liposomes—when using the traditional isolation methods that separate according to size and density. Abstract : Blood contains various biological nanoparticles, including lipoproteins and extracellular vesicles. We highlight that these lipid–protein based nanoparticles can challenge protein corona studies on nanomedicines—with particular focus on liposomes—when using isolation methods that separate according to size and density. Key: high‐, low‐, and very low‐density lipoproteins (HDL, LDL, and VLDL), chylomicron (CM), extracellular vesicle (EV).